2014
DOI: 10.1089/aid.2013.0203
|View full text |Cite
|
Sign up to set email alerts
|

Increased CXCR4 Use of HIV-1 Subtype C Identified by Population Sequencing in Patients Failing Antiretroviral Treatment Compared with Treatment-Naive Patients in Botswana

Abstract: HIV-1 uses the coreceptors CCR5 and/or CXCR4 for cell entry. Monotropic CCR5-using variants are found early in the infection while CXCR4-using variants may appear after progression to AIDS. CXCR4 use may consist of both monotropic and dualtropic viruses. The viral phenotype is important in evaluating the response to CCR5 inhibitors, a new class of antiviral drugs. The coreceptor use of HIV-1 was investigated using population sequencing in 24 patients from Botswana, carrying HIV-1 subtype C and failing antiretr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 256 publications
(461 reference statements)
0
8
1
Order By: Relevance
“…Some recent studies from South Africa and India also showed predominance of R5 strains in treatment naïve as well as experienced HIV-1C infected patients [12], although a South African study reported predominance of X4 strains in treatment experienced children [13]. More recently, a higher incidence of X4-tropic HIV-1C were described in patients with advanced immunodeficiency from South Africa, India and Botswana, respectively [1417]. However, recent tropism data from patients with progressive HIV-1C ET infection is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent studies from South Africa and India also showed predominance of R5 strains in treatment naïve as well as experienced HIV-1C infected patients [12], although a South African study reported predominance of X4 strains in treatment experienced children [13]. More recently, a higher incidence of X4-tropic HIV-1C were described in patients with advanced immunodeficiency from South Africa, India and Botswana, respectively [1417]. However, recent tropism data from patients with progressive HIV-1C ET infection is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Viruses using the CXCR4 coreceptor are referred to as X4-tropic viruses. In some cases, viruses use both the CCR5 and the CXCR4 coreceptors (i.e., dual-tropic viruses) [ 3 ]. In the early stage of HIV-1, viruses predominantly use CCR5 but can switch to CXCR4 at an advanced stage of the disease [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the early stage of HIV-1, viruses predominantly use CCR5 but can switch to CXCR4 at an advanced stage of the disease [ 4 , 5 ]. CXCR4 usage increases among patients on antiretroviral treatment (ART) [ 3 , 6 , 7 ]. A coreceptor switch to CXCR4 is associated with higher pathogenicity and has been reported in ~50% of HIV-1 subtype B infections but is rare and under-studied in subtype C infection [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant majority of the initial infecting HIV-1-C viruses utilize CCR5. However, the presence of a significant proportion of CXCR4 utilizing viruses (X4) in chronic HIV-1-C infection [32][33][34] might compromise the effectiveness of CCR5 antagonists, such as Maraviroc, when included as components in salvage therapy. In the current analyses, co-receptor preference in early and chronic HIV-1-C infections across Africa was examined, using sequences from the Los Alamos HIV Sequence Database, with the view of understanding the co-receptor preference landscape of the epidemiologically important HIV-1-C across the continent.…”
mentioning
confidence: 99%